Involvement of S-nitrosylation of actin in inhibition of neurotransmitter release by nitric oxide - Oishi Yo; Okuda-Ashitaka Emiko; Katano Tayo; Lu Jingshan; Urade Yoshihiro; Ito Seiji (SAGE Publishing, 2009)
Abstract Background The role of the diffusible messenger nitric oxide (NO) in the regulation of pain transmission is still a debate of matter, pro-nociceptive and/or anti-nociceptive. S-Nitrosylation, the reversible post-translational modification of selective cysteine residues in proteins, has emerged as an important mechanism by which NO acts as a signaling molecule. The occurrence of S-nitrosylation in the spinal cord and its targets that may modulate pain transmission remain unclarified. The "biotin-switch" method and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry were employed for identifying S-nitrosylated proteins. Results Here we show that actin was a major protein S-nitrosylated in the spinal cord by the NO donor, S-nitroso-N-acetyl-DL-penicillamine (SNAP). Interestingly, actin was S-nitrosylated, more in the S2 fraction than in the P2 fraction of the spinal homogenate. Treatment of PC12 cells with SNAP caused rapid S-nitrosylation of actin and inhibited dopamine release from the cells. Just like cytochalasin B, which depolymerizes actin, SNAP decreased the amount of filamentous actin cytoskeleton just beneath the membrane. The inhibition of dopamine release was not attenuated by inhibitors of soluble guanylyl cyclase and cGMP-dependent protein kinase. Conclusion The present study demonstrates that actin is a major S-nitrosylated protein in the spinal cord and suggests that NO directly regulates neurotransmitter release by S-nitrosylation in addition to the well-known phosphorylation by cGMP-dependent protein kinase.